The use of compost in afforestation of Mediterranean areas: Effects on soil properties and young tree seedlings. - Larchevêque, Marie; Ballini, Christine; Korboulewsky, Nathalie; Montès, Nicolas (The Science of the total environment, 2006)
In Mediterranean frequently burnt areas, fire and erosion result in the decrease of soil fertility, so afforestation is a major concern. We carried out an in situ experiment of compost amendment to improve survival and growth of planted tree seedlings. One-year-tree seedlings of native species (Quercus ilex, Pinus halepensis and Pinus pinea) were planted on a frequently burnt calcareous site. Three rates of fresh co-composted sewage sludge and greenwastes (control without compost, 20 and 40 kg m(-2) of compost) were incorporated into the soil at each seedling stem. Changes of soil properties and tree development were studied during 3 years (2001-2003) and 2 years (2002-2003) respectively. The compost improved survival of Quercus ilex and Pinus pinea seedlings in severe drought conditions, but had no effect on Pinus halepensis. For all species seedling length and radial growth and NPK nutrition were increased for both rates of amendment. Amendment improved soil fertility, but available P concentration increased 13 fold in the neighbouring soil of seedlings amended at the maximal rate compared to control. However, amendment did not significantly increase concentrations of Cd, Cr, Ni and Pb in soils or tree seedlings. It increased Cu and Zn total and available concentrations in soils, while foliar Cu and Zn concentrations in the seedlings remained similar in all plots. Compost can efficiently help afforestation of dry soils with low organic matter content. However, sewage sludge concentrations in P, and to a lesser extent in Cu and Zn, limit rates of application that can be applied without environmental hazard.
Keywords: Afforestation; Pinus halepensis; Pinus pinea; Quercus ilex; Sewage sludge compost; Trace metals

The use of compost in afforestation of Mediterranean areas: Effects on soil properties and young tree seedlings. - Larchevêque, Marie; Ballini, Christine; Korboulewsky, Nathalie; Montès, Nicolas (The Science of the total environment, 2006)
In Mediterranean frequently burnt areas, fire and erosion result in the decrease of soil fertility, so afforestation is a major concern. We carried out an in situ experiment of compost amendment to improve survival and growth of planted tree seedlings. One-year-tree seedlings of native species (Quercus ilex, Pinus halepensis and Pinus pinea) were planted on a frequently burnt calcareous site. Three rates of fresh co-composted sewage sludge and greenwastes (control without compost, 20 and 40 kg m(-2) of compost) were incorporated into the soil at each seedling stem. Changes of soil properties and tree development were studied during 3 years (2001-2003) and 2 years (2002-2003) respectively. The compost improved survival of Quercus ilex and Pinus pinea seedlings in severe drought conditions, but had no effect on Pinus halepensis. For all species seedling length and radial growth and NPK nutrition were increased for both rates of amendment. Amendment improved soil fertility, but available P concentration increased 13 fold in the neighbouring soil of seedlings amended at the maximal rate compared to control. However, amendment did not significantly increase concentrations of Cd, Cr, Ni and Pb in soils or tree seedlings. It increased Cu and Zn total and available concentrations in soils, while foliar Cu and Zn concentrations in the seedlings remained similar in all plots. Compost can efficiently help afforestation of dry soils with low organic matter content. However, sewage sludge concentrations in P, and to a lesser extent in Cu and Zn, limit rates of application that can be applied without environmental hazard.
The following values have no corresponding Zotero field: accession-num: 16762400
Keywords: Afforestation; Pinus halepensis; Pinus pinea; Quercus ilex; Sewage sludge compost; Trace metals

Higher plants as bioindicators of sulphur dioxide emissions in urban environments. - Hijano, Concepción Fidalgo; Domínguez, Maria Dolores Petit; Gimínez, Rosario García; Sínchez, Pilar Hungría; García, Inís Sancho (Environmental monitoring and assessment, 2005)
The evaluation of certain vascular plants that grow in the city of Madrid as biomonitors of SO(2) air pollution in urban environments has been carried out. Total concentration of sulphur in leaves of the chosen higher plants as well as other parameters in close relation to this contaminant (visible injury symptoms, chlorophyll a- and b-content and peroxidase activity) have been determined in order to study the spatial distribution and temporal changes in SO(2) deposition. Results obtained show that coniferous species such as Pinus pinea, were more sensitive to SO(2) atmospheric concentration than leafy species as Quercux ilex subspecies ballota and, in the same way, bush species, such as Pyracantha coccinea and Nerium oleander, were more sensitive than wooded species, such as Cedrus deodara and Pinus pinea, respectively. There is a higher accumulation of sulphur in vegetable species located near highways and dense traffic incidence roads and near areas with high density of population. The minimum values for accumulation of SO(2) were registered in winter and spring seasons (from January to April) due to the vegetative stop; while maximum values are obtained during the summer season (from June to September), due to the stoma opening. The highest increments in sulphur concentration, calculated as the difference between two consecutive months, are obtained in May and June for all considered species except for Cedrus deodara and Pyracantha coccinea, both species have few seasonal changes during the whole year. Some species are more sensitive to natural washing than others, showing a decrease in sulphur concentration after rainfall periods.
Keywords: atmospheric pollution; Bioindicators; Cedrus deodara; higher plants; Nerium oleander; Pinus pinea; Pyracantha coccinea; Quercus ilex; Sulphur dioxide

Growth of forest plants (pine and holm-oak) inoculated with rhizobacteria: relationship with microbial community structure and biological activity of its rhizosphere - Garcı́a, Jose A.Lucas; Domenech, Jezabel; Santamarı́a, Carmen; Camacho, Marı́a; Daza, Antonio; Mañero, F.Javier Gutierrez (Environmental and Experimental Botany, 2004)
Four bacterial strains showing in vitro metabolic capacities related to their plant growth-promoting action (plant growthpromoting rhizobacteria (PGPRs)) were studied in the growth of holm-oak (Quercus ilex ssp. Ballota) and pine (Pinus pinea) plants at a forest nursery before outplanting. All strains signiﬁcantly increased some of the parameters studied (stem length, neck diameter and shoot dry weight), although, neck root diameter showed the smallest increase in general. An interaction plant/bacterial strain was observed. Some strains speciﬁcally increased aerial parameters in both plant species, whereas other strains did so mainly in one plant species. Analyses of PLFAs and incorporation of thymidine and leucine suggest differences in the perturbation of microbial communities previously established and in the capacity of adaptation to the rhizosphere environment among the different strains
Keywords: colonisation; PGPR; Pinus pinea; plfas; Quercus ilex ssp. ballota; rhizosphere; thymidine leucine incorporation

Growth of forest plants (pine and holm-oak) inoculated with rhizobacteria: relationship with microbial community structure and biological activity of its rhizosphere - Garcı́a, Jose A. Lucas; Domenech, Jezabel; Santamarı́a, Carmen; Camacho, Marı́a; Daza, Antonio; Mañero, F. Javier Gutierrez (Environmental and Experimental Botany, 2004)
Four bacterial strains showing in vitro metabolic capacities related to their plant growth-promoting action (plant growthpromoting rhizobacteria (PGPRs)) were studied in the growth of holm-oak (Quercus ilex ssp. Ballota) and pine (Pinus pinea) plants at a forest nursery before outplanting. All strains signiﬁcantly increased some of the parameters studied (stem length, neck diameter and shoot dry weight), although, neck root diameter showed the smallest increase in general. An interaction plant/bacterial strain was observed. Some strains speciﬁcally increased aerial parameters in both plant species, whereas other strains did so mainly in one plant species. Analyses of PLFAs and incorporation of thymidine and leucine suggest differences in the perturbation of microbial communities previously established and in the capacity of adaptation to the rhizosphere environment among the different strains
Keywords: colonisation; PGPR; Pinus pinea; plfas; Quercus ilex ssp. ballota; rhizosphere; thymidine leucine incorporation

Breeding performance of the Blue Tit Parus caeruleus in a patchy Mediterranean landscape - Catalan, R M; Haeger, J F (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
This study compares reproductive strategy and breeding success of Parus caeruleus in a helm-oak (Quercus rotundifolia) forest and a pine plantation (Pinus pinea and P. pinaster) in the southern Iberian Peninsula. During the breeding period, an asymmetric flow of individuals takes place from the helm-oak forest to the pine plantation. This flow is favoured by nestboxes where Blue tits can lay their eggs. During the winter, a large part of the population moves back from the pine plantation to the helm-oak forest. Breeding pair density was much higher in the helm-oak forest than in the pine plantation. This may bt accounted for by the poorer quality of the resources available in the pine plantation which birds try to compensate for with larger breeding territories. Breeding density and most life-history traits examined (timing of breeding, clutch site, egg size, number of fledglings and fledgling weight) were similar in both habitats, as a result of the phenotypic plasticity of this species. Although breeding success was similar in both habitats, recruitment of new individuals per unit area was higher in the helm-oak forest. The consequences of pine plantations, as a form of forestry management, on species conservation is discussed.
APS
Keywords: breeding success; Holm oak; iberian peninsula; Parus caeruleus; Pinus pinaster; Pinus pinea; Quercus ilex; reproductive strategies

Effect of habitat and age on variations in volatile organic compound (VOC) emissions from Quercus ilex and Pinus pinea - Street, R A; Owen, S; Duckham, S C (Atmospheric Environment, 1997)
A dynamic branch enclosure was used to measure emission rates of volatile organic compounds (VOCs) under field conditions from two common native Mediterranean species, Quercus ilex and Pinus pinea. In addition to a-pinene, B-pinene, sabinene, limonene and cineole, a suite of lesser known compounds were tentatively identified including cis- and trans-ocimene, cis- and trans-linalool oxide and sabinaketone. Emissions of isoprene from Quercus ilex were insignificant in comparison to those of the monoterpenes and were not detected from Pinus pinea. Variability in emission rates between two habitats, the forest and the dunes, were assessed for Quercus ibex. Temperature sensitivities of emissions and total summed emission rates from Quercus ilex were clearly related to environmental conditions. Emission rates from Pinus pinea showed great variability, but differences between normalised mean emission rates from mature forest and young plantation trees may be significant. Existing emission rate models were found to inadequately describe the observed data.
Keywords: Biogenic emissions; branch enclosure; Mediterranean vegetation; Monoterpene; Pinus pinea; Quercus ilex; VOCs

Screening of 18 Mediterranean plant species for volatile organic compound emissions - Owen, S; Boissard, C; Street, R A; Duckham, S C; Csiky, O; Hewitt, C N (Atmospheric Environment, 1997)
Eighteen tree and shrub species were screened for emissions of isoprene and other volatile organic compounds (VOCs) at three locations at Castelporziano (Italy) using a bag-enclosure sampling method followed by GC analysis. Thirty emitted compounds were identified. Temperature sensitivity of emissions of monoterpenes varied between species. Strong temperature dependencies were found for isoprene emissions. For monoterpene-emitting plant species with greatest ground cover in the dunes and macchia habitats, α-pinene, β-pinene and sabinene appeared to be the most frequently and abundantly emitted compounds. Isoprene was the major emission from the shrub species screened in the forest. Emissions from four dominant plant species were scaled up to estimate total fluxes from the dunes and macchia over a daytime period. Species with greatest biomass but low emission rates made a substantial contribution to total emissions.
Keywords: Arbutus unedo; Biogenic emissions; branch enclosure; Chrysanthemum praecox; cistus incanus; Cistus salvifolius; Cytisus sp.; Dittrichia sp.; Erica arborea; Erica multiflora; Helichrysum stoechas; isoprene; Juniperus oxycedrus; Juniperus phoenicea; Monoterpene; myrtus communis; Phillyrea angustifolia; Pinus pinea; Quercus cerris; Quercus ilex; Rubus fruticosus; Spartium junceum; VOCs

The efficiency of nitrogen retranslocation from leaf biomass in Quercus ilex ecosystems - Escudero, a; Arco, J M; Garrido, M V (Plant Ecology, 1992)
Nitrogen retranslocation from senescing leaves represents a crucial adaptation by tree species towards a more efficient use of this nutrient. As a result, this part of the nitrogen cycle has received increasing attention in recent years. However, there remain strong discrepancies with respect to the factors re- sponsible for interspecific differences in the efficiency of this process. In the present work the seasonal pattern of leaf growth and the movement of nitrogen in leaves have been studied in a series of Quercus ilex plots with different levels of rainfall and soil quality in central- western Spain, as well as in 20 other woody species typical of this area. The percentage of nitrogen retranslocated was estimated from the difference between the maximum mass of nitrogen stored in the leaf biomass and the amount of this nutrient returned annually to the soil through leaf fall. Q. ilex appears as one of the least efficient species in the Mediterranean region in the recovery of nitrogen from senescing leaves (29.7°0 of the maximum pool). Furthermore, the older leaves of Q. ilex do not s h o w the cycles of nitrogen withdrawal during new flushes of shoot growth, such as occurs in Pinus spp. This suggests that older leaves in Q. ilex do not play an important role as nitrogen storage organs.
Keywords: leaf demography; Leaf fall; nutrient cycling; Pinus pinea; Quercus ilex; Quercus pyrenaica